2015
DOI: 10.1007/s10530-015-0896-1
|View full text |Cite
|
Sign up to set email alerts
|

Invasion genetics of the Pacific oyster Crassostrea gigas in the British Isles inferred from microsatellite and mitochondrial markers

Abstract: Abstract:The Pacific oyster, Crassostrea gigas, native to northeast Asia, is one of the most important cultured shellfish species. In Europe, Pacific oysters first settled along the Atlantic coasts of France at the end of the 1960s but rapidly spread and are now widely established. Twenty-two sites in the United Kingdom (UK), Ireland, Denmark, France and Spain were sampled to assess genetic diversity and differentiation. Hatcherypropagated stocks from two hatcheries located in the UK also were included. Two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 69 publications
6
39
2
Order By: Relevance
“…However, only weak general patterns in heterozygote deficiency across samples or populations were observed: the Irish aquaculture sample showed a pattern of consistent deficit across loci indicative of inbreeding or a Wahlund effect (when a sampled 'population' is a mixture of different subpopulations; Wahlund 1928). Although hetero zygote deficiency was observed in some of the samples, both H o and H e were relatively high for all samples across all loci, in agreement with previous studies performed on Crassostrea gigas (Li et al 2006, Kochmann et al 2012, Rohfritsch et al 2013, Lallias et al 2015. On the other hand, when considering N a and A R , higher genetic diversity was ob served in the southern group.…”
Section: Genetic Diversity Patternssupporting
confidence: 89%
See 2 more Smart Citations
“…However, only weak general patterns in heterozygote deficiency across samples or populations were observed: the Irish aquaculture sample showed a pattern of consistent deficit across loci indicative of inbreeding or a Wahlund effect (when a sampled 'population' is a mixture of different subpopulations; Wahlund 1928). Although hetero zygote deficiency was observed in some of the samples, both H o and H e were relatively high for all samples across all loci, in agreement with previous studies performed on Crassostrea gigas (Li et al 2006, Kochmann et al 2012, Rohfritsch et al 2013, Lallias et al 2015. On the other hand, when considering N a and A R , higher genetic diversity was ob served in the southern group.…”
Section: Genetic Diversity Patternssupporting
confidence: 89%
“…Several populations showed deviations from HW proportions in the form of heterozygote deficiency, consistent with previous studies of the Pacific oyster (Meistertzheim et al 2013, Rohfritsch et al 2013, Lallias et al 2015. However, only weak general patterns in heterozygote deficiency across samples or populations were observed: the Irish aquaculture sample showed a pattern of consistent deficit across loci indicative of inbreeding or a Wahlund effect (when a sampled 'population' is a mixture of different subpopulations; Wahlund 1928).…”
Section: Genetic Diversity Patternssupporting
confidence: 86%
See 1 more Smart Citation
“…For example, it is documented that C. angulata was introduced into Morocco from Spain and Portugal in 1952(Shafee 1985cited in Fabioux et al 2002. In contrast to C. gigas in Europe, which showed a typical star-shaped haplotype phylodiversity characteristic of expanding populations (Moehler et al 2011;Lallias et al 2015), the haplotype network of C. angulata did not show such a pronounced star-shape. Significant negative Tajima's D values were only found for C. angulata samples from Asia, although Fu's F tests were significant for Mira and Keelung samples.…”
Section: Discussioncontrasting
confidence: 60%
“…The nucleotide diversity of C. angulata observed in the present study was higher than that previously reported for C. gigas for the same mitochondrial region. Moehler et al (2011) and Lallias et al (2015) reported nucleotide diversity values of 0.0044 and 0.0046 for C. gigas, respectively, with samples mainly collected in Europe but also in Canada and Japan. Hsiao et al (2016) found haplotype and nucleotide diversities (using mitochondrial cytochrome oxidase I sequences) in Asia being considerably higher in C. angulata than in C. gigas.…”
Section: Discussionmentioning
confidence: 99%